Modeling of wave-induced irradiance variability in the upper ocean mixed layer - M. Hieronymi; A. Macke; O. Zielinski (Ocean Science, 2012)
A Monte Carlo based radiative transfer model has been developed for calculating the availability of solar radiation within the top 100 m of the ocean. The model is optimized for simulations of spatial high resolution downwelling irradiance Ed fluctuations that arise from the lensing effect of waves at the water surface. In a first step the accuracy of simulation results has been verified by measurements of the oceanic underwater light field and through intercomparison with an established radiative transfer model. Secondly the potential depth-impact of nonlinear shaped single waves, from capillary to swell waves, is assessed by considering the most favorable conditions for light focusing, i.e. monochromatic light at 490 nm, very clear oceanic water with a low chlorophyll a content of 0.1 mg m−3 and high sun elevation. Finally light fields below irregular wave profiles accounting for realistic sea states were simulated. Our simulation results suggest that under open ocean conditions light flashes with 50% irradiance enhancements can appear down to 35 m depth, and light variability in the range of ±10% compared to the mean Ed is still possible in 100 m depth.